2020
DOI: 10.3390/ma13245651
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Electrospun Fibers Containing Bioactive Glass Particles for Wound Healing

Abstract: Chitosan fibers blended with polyethylene oxide (CHIT_PEO) and crosslinked with genipin were fabricated by electrospinning technique. Subsequently, CHIT_PEO bioactive glass composite electrospun mats were fabricated with the aim to achieve flexible structures with adequate mechanical properties and improved biological performance respect to CHIT_PEO fibers, for potential applications in wound healing. Three different compositions of bioactive glasses (BG) were selected and investigated: 45S5 BG, a Sr and Mg co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…The financial burden is higher than the $25 billion/year spent on CNHW treatment in just the United States [ 1 ]. Therefore, numerous attempts have been made to manage CNHW, including the use of traditional wound dressings (e.g., gauze and ointments) and advanced dressings (e.g., biodegradable and biocompatible materials) [ 2 , 3 ]. However, bacterial infections are still among the most challenging issues ahead of treating CNHW in the clinic and may impede wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The financial burden is higher than the $25 billion/year spent on CNHW treatment in just the United States [ 1 ]. Therefore, numerous attempts have been made to manage CNHW, including the use of traditional wound dressings (e.g., gauze and ointments) and advanced dressings (e.g., biodegradable and biocompatible materials) [ 2 , 3 ]. However, bacterial infections are still among the most challenging issues ahead of treating CNHW in the clinic and may impede wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the findings demonstrated that the tensile strain at break of GC‐Ch/PEO/Gel and Ag/GC‐Ch/PEO/Gel nanofibrous scaffolds enhanced, compared to Ch/PEO/Gel nanofibrous scaffold, showing that the nanocomposites possess higher mechanical properties than neat nanofibers (Figure 3a). This can be related to the impairing effect of particles such as GCs on the structure of the polymeric scaffolds by serving as hard inclusions 28,29 …”
Section: Resultsmentioning
confidence: 99%
“…This can be related to the impairing effect of particles such as GCs on the structure of the polymeric scaffolds by serving as hard inclusions. 28,29 Thermal gravimetric analysis (TGA) measures the weight change of a sample as a function of temperature, while subjected to a controlled heating program. Figure 3b,c show TG and DTG thermograms of Ch/PEO/Gel, GC-Ch/PEO/Gel, and the Ag/GC-Ch/PEO/Gel F I G U R E 1 (a) GC and Ag/GC synthesis by the sol-gel method (b) GC-Ch/PEO/Gel and Ag/GC-Ch/PEO/Gel nanofibrous scaffold fabrication through electrospinning samples.…”
Section: Structural Characterization Of Scaffoldsmentioning
confidence: 99%
“…These substances have shown great promise in managing both acute and chronic wounds, and their emerging applications in treating skin malignancies are still under evaluation [ 17 ]. Bioactive glasses were previously proven as suitable additives for promoting different stages of skin wounds [ 42 , 43 ]. Up to now, various formulations of bioactive glasses, including silicate-, phosphate-, as well as borate- and borosilicate-based glasses, have been investigated in treating skin injuries with promising outcomes [ 44 , 45 , 46 ].…”
Section: Current Therapies In Managing Wounds and The Potential Of Mesoporous Materialsmentioning
confidence: 99%